"Defining Ourselves for Ourselves": Black Girls Conceptualize Black Girlhood Online. Issue 3 (1st December 2022) - Kaler-Jones, Cierra
Abstract: Black girls have long created their own subversive and creative forms of curriculum and pedagogy. I explore adolescent Black girls' suggestions for teaching and learning about Black girlhood online based on a virtual summer arts program called Black Girls S.O.A.R. Through performance ethnography, we contended with our conceptualizations of Black girlhood and identity sense-making. The co-researchers suggested that storytelling, learner-centered pedagogy, and intentional community-building must be central in virtual pedagogy and saw reclaiming girlhood and self-care as two essential topics for teaching Black girlhood content. I also reflect on the tensions and possibilities of co-constructing participatory learning environments with Black girls, particularly as it relates to disrupting power and adultism.